Agama Pra-Islam Perspektif Al-Qur’an - Anggraeni, Dewi (Jurnal Studi Al-Qur’an, 2016)
This paper discusses how the Qur’an speaks of pre-Islamic religions which originally came from a monotheistic religion whose brought by Abraham. Explicitly the Qur’an gives the message essentially the same message between the Qur’an and the earlier books. This message give a signals the continuity of God’s message in which all the semitic religions revealed in the Qur’an lead to the prophet Abraham. So the semitic religions have the same mission to purify Tauhid as a peace religion based on submission to God. At once refine again the belief of those who believe in supernatural powers that are limited to the beliefs of myth. Finally the coming of the prophet Muhammad was to support, confirm, rectify, and perfecting the teachings of the former religion. Keywords : Religions, Pre-Islamic, Monotheistic. Abstrak Tulisan ini membahas tentang bagaimana al Quran membicarakan agama-agama pra- Islam yang awalnya berasal dari satu agama monoteisme yang di bawa oleh Ibrahim. Secara eskplisit al-Qurâ€™an memberikan pesan secara esensial adanya pesan yang sama antara al-Qurâ€™an dengan kitab-kitab sebelumnya. Pesan ini memberikan isyarat adanya keseinambungan risalah Tuhan dimana semua agama semitik yang diungkap dalam al-Qurâ€™an bermuara kepada nabi Ibrahim As. Sehingga agama-agama semitik memiliki misi yang sama untuk memurnikan Tauhid sebagai agama kedamaian yang berlandaskan kepasrahan kepada Tuhan. Sekaligus memurnikan kembali kepercayaan orang-orang yang meyakini kekuatan adikodrati yang hanya sebatas keyakinan dari mitos. Akhirnya kedatangan nabi Muhammad adalah untuk mendukung, mengukuhkan, meluruskan kembali, dan menyempurnakan ajaran-ajaran agama terdahulu. Kata Kunci : Agama, Pra-Islam,Monoteisme